Paternal grandmother's smoking in pregnancy is associated with extreme aversion to bitter taste in their grandchildren. Issue 1 (16th February 2022) - Golding, Jean; Pembrey, Marcus E; Gregory, Steven; Suderman, Matthew; Iles-Caven, Yasmin; Northstone, Kate
Abstract: Although there are many examples in the experimental literature of an environmental exposure in one generation impacting the phenotypes of subsequent generations, there are few studies that can assess whether such associations occur in humans. The Avon Longitudinal Study of Parents and Children (ALSPAC) has, however, been able to determine whether there are associations between grandparental exposures and their grandchildren's development. Several of our studies, including sensitivity to loud noise, have shown associations between a grandmother smoking in pregnancy and the phenotype of the grandchild. These results were mostly specific to the sex of the grandchild and to whether the prenatal (i.e. during pregnancy) smoking occurred in the maternal or paternal grandmother. Here, we have used ancestral data on prenatal smoking among the grandmothers of the ALSPAC index children to examine possible effects on the grandchild's ability to detect the bitter taste of PROP (6 n -propylthiouracil), distinguishing between the 10% deemed 'extreme tasters', and the rest of the population (total N = 4656 children). We showed that grandchildren whose paternal (but not maternal) grandmothers had smoked in pregnancy were more likely than those of non-smoking grandmothers to be extreme tasters [odds ratio (OR) 1.28; 95% confidence interval (CI) 1.03, 1.59] and that this was more likely in granddaughters (OR 1.42; 95% CI 1.03, 1.95) than grandsons (OR 1.18; 95% CI 0.88, 1.60). This pattern of association between paternal foetal exposure and the granddaughter's development has been found with several other outcomes, suggesting that investigations should be undertaken to investigate possible mechanisms.